Design and fabrication of adjustable work positioner - Mohamad Nafis, Jamaluddin (2011)
The objective of this project is to design and fabricate an adjustable work positioner. Adjustable work positioner is important equipment because it reduces the work area of a person and provides a practical and suitable place to put their tools while working. However, the current adjustable work positioners do not have enough safety characteristic that can covert the user from danger which there is sharp edges on the product. They also have a low level of stability which increases the risk of falling when using the adjustable work positioner. That is the main reason why we need a concept of the adjustable work positioner. The main features of this adjustable work positioner are the platform that can be set to the most convenient height and tilted to a specific angle that the user desires. The idea was appear because of the lack of adjustability in the existing products. The idea of the fabrication of this adjustable work positioner is based on student’s creativity. The selection of suitable materials in the fabricating of this adjustable work positioner is a loaded material which has suitable weight; long life-span and can detain large force. Materials are proposed for the fabrication of the adjustable work positioner is mild steel material. There are several processes involved during the design and fabrication of this adjustable work positioner which are consisted in this report.